Physical Condition Level and Survey of the West Java PSSI Referee Training Program - Zulkifli, Syahrul; Syamsudar, Bangbang (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aims to determine the physical condition of football referees under PSSI West Java, divided into four zones: Purwasukasi, Priangan, Pantura, and Bandung Raya. This descriptive quantitative study employed the FIFA Fitness Test and a brief survey to evaluate referees' physical literacy and training programs. A total of 220 referees participated, with pass rates of 32% in Purwasukasi, 24% in Priangan, 52% in Pantura, and 52% in Bandung Raya. The results revealed differences among zones due to variations in training culture, facility support, and referee engagement. Referees in Pantura and Bandung Raya received more structured training programs, whereas those in Purwasukasi and Priangan received irregular training with limited access to standardized programs. These differences also reflect variations in physical literacy. The failure in the interval test indicates low aerobic endurance, which may affect decision-making during matches. To address this, implementing structured conditioning such as the FIFA 11+ Referees Program is recommended to improve fitness, endurance, and injury prevention. The findings serve as evaluation material for PSSI West Java to enhance referee development and performance standards.